Monopolizing Violence and Consolidating Power* - Powell, Robert (Quarterly Journal of Economics, 2013)
Governments in weak states often face an armed opposition and have to decide whether to try to accommodate and contain that adversary or to try to consolidate power and monopolize violence by disarming it. When and why do governments choose to consolidate power and monopolize violence? How fast do they try to consolidate power? When does this lead to costly fighting rather than to efforts to eliminate the opposition by buying it off? We study an infinite-horizon model in which the government in each period decides how much to offer the opposition and the rate at which it tries to consolidate its power. The opposition can accept the offer and thereby acquiesce to the government’s efforts to consolidate, or it can fight in an attempt to disrupt those efforts. In equilibrium, the government always tries to monopolize violence when it has “coercive power” against the opposition where, roughly, coercive power is the ability to weaken the opposition by lowering its payoff to fighting. Whether the government consolidates peacefully or through costly fighting depends on the size of any “contingent spoils,” which are benefits that begin to accrue from an increase in economic activity resulting from the monopolization of violence and the higher level of security that comes with it. When contingent spoils are small, the government buys the opposition off and eliminates it as fast as is peacefully possible. When contingent spoils are large, the government tries to monopolize violence by defeating the opposition militarily.